Exploration of interaction zones of β-tubulin colchicine binding domain of helminths and binding mechanism of anthelmintics. (June 2017) - Ranjan, Prabodh; Kumar, Sivakumar Prasanth; Kari, Vijayakrishna; Jha, Prakash Chandra
Graphical abstract: Highlights: Postulated the possible modes of anthelminthic activity and its underlying resistance mechanisms. Identification of three interaction zone of colchicine binding domain of H. contortus β-tubulin homology model using protein-ligand interaction fingerprints. Zone-2 anthelmintic structure-based pharmacophore models proposed using dock conformations of β-tubulin anthelmintics and inhibitors. Abstract: Numerous studies postulated the possible modes of anthelmintic activity by targeting alternate or extended regions of colchicine binding domain of helminth β-tubulin. We present three interaction zones (zones vide −1 to −3) in the colchicine binding domain of Haemonchus contortus (a helminth) β-tubulin homology model and developed zone-wise structure-based pharmacophore models coupled with molecular docking technique to unveil the binding hypotheses. The resulted ten structure-based hypotheses were then refined to essential three point pharmacophore features that captured recurring and crucial non-covalent receptor contacts and proposed three characteristics necessary for optimal zone-2 binding: a conserved pair of H bond acceptor (HBA to form H bond with Asn226 residue) and an aliphatic moiety of molecule separated by 3.75 ± 0.44 Å. Further, an aliphatic or a heterocyclic group distant (11.75 ± 1.14 Å) to the conserved aliphatic site formed the third feature component in the zone-2 specific anthelmintic pharmacophore model. Alternatively, an additional HBA can be substituted as a third component to establish H bonding with Asn204. We discern that selective zone-2 anthelmintics can be designed effectively by closely adapting the pharmacophore feature patterns and its geometrical constraints.